2003
DOI: 10.1245/aso.2003.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Vascular Endothelial Growth Factor, Basic Fibroblast Growth Factor, and Angiogenin in Patients With Resectable Hepatocellular Carcinoma After Surgery

Abstract: Preoperative serum VEGF is a significant independent predictor of tumor recurrence, DFS, and OS in patients with resectable HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(112 citation statements)
references
References 38 publications
5
102
0
5
Order By: Relevance
“…It has been reported previously that in normal liver cells, the level and intensity of VEGF is not detectable (4,18,30,32). We found that VEGF was undetectable in the low-grade HCC tumors that we assayed.…”
Section: Expression Levels Of Prb2/p130 P27mentioning
confidence: 90%
See 1 more Smart Citation
“…It has been reported previously that in normal liver cells, the level and intensity of VEGF is not detectable (4,18,30,32). We found that VEGF was undetectable in the low-grade HCC tumors that we assayed.…”
Section: Expression Levels Of Prb2/p130 P27mentioning
confidence: 90%
“…Usually, HCC arises from an adenomatous hyperplasia in an already diseased liver and progresses from a well-differentiated stage to less-differentiated forms (3). Ordinary HCCs formed by progression show highly increased cellular proliferation, neovascularization, production of basic fibroblast growth factor, and aneuploidy in some tumors (4). Corresponding to its malignant progression, HCCs show loss of heterozygosity for multiple chromosomes (5).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increased VEGF expression has been reported in cirrhotic and dysplastic liver tissue, suggesting a possible role for VEGF-mediated angiogenesis in hepatocarcinogenesis (El-Assal et al, 1998). VEGF clearly has an important regulatory role in HCC; high levels of VEGF expression have been linked with HCC tumor grade , poor outcome after resection (Poon et al, 2004b), disease recurrence, poor disease-free and overall survival (OS) (Chao et al, 2003), vascular invasion (Li et al, 1998) and portal vein emboli (Zhou et al, 2000).…”
Section: Vegf Receptor Signalingmentioning
confidence: 99%
“…In total, there were four tissue OS studies (Chow et al, 1997;Jeng et al, 2004a;Deli et al, 2005;Sheen et al, 2005), six tissue DFS studies (Jeng et al, 2004a;Sheen et al, 2005;Guo et al, 2006;Wada et al, 2006;Zhang et al, 2006;Ho et al, 2007), seven serum OS studies (Poon et al, 2001(Poon et al, , 2004a(Poon et al, , b, 2007Chao et al, 2003;Kim et al, 2004;Jeng et al, 2004b;Treiber et al, 2006), and five serum DFS studies (Poon et al, 2001(Poon et al, , 2007Chao et al, 2003;Jeng et al, 2004b;Treiber et al, 2006). Pooled HRs were then calculated for all groups.…”
Section: Summary Estimates Of Primary Studiesmentioning
confidence: 99%